The Effect of Welding Current on the Mechanical Properties of AISI 1040 Steel and AISI 1020 Steel in Bimetal Welding Using the Shielded Metal Arc Welding Method with AWS E 7016 Electrodes - Aditya Angga Wijaya; Tarkono; Irza Sukmana; Rizal Nazarrudin; Joy Rizki Pangestu Djuansjah (Engineering Forum of Western Indonesian Government Universities Board (Forum Teknik, BKS-PTN Wilayah Barat) Indonesia, 2025)
This article discusses bimetal welding between AISI 1040 steel and AISI 1020 steel using the Shielded Metal Arc Welding (SMAW) method with AWS E 7016 electrodes. The purpose of the study was to evaluate the quality of the welded joint, including the mechanical properties and microstructure of the bimetal welding results. The use of high-strength AISI 1040 steel and AISI 1020 steel with malleable properties aims to produce a joint that optimizes the characteristics of each material. The welding process was carried out with varying current parameters to determine its effect on the welding results. Testing included tensile testing, hardness testing, impact testing, and microstructure analysis. The results showed that variations in welding parameters affected the mechanical properties of the joint and the distribution of microstructures in the weld zone, heat-affected zone (HAZ), and base metal. The optimal welded joint was obtained by setting certain current parameters that produced maximum tensile strength and even hardness distribution. This study contributes to the development of bimetal welding technology, especially for applications that require a combination of mechanical properties of two types of steel.